Russian Current Associated with Ultrasound or Phonophoresis Reduces Cellulite - Rodrigues, Anna Y. M. (2018)
Introduction: Geloid fibroedema (GF) or Cellulitis causes local deformations in the subcutaneous tissue. Electric Stimulation Therapy, such as the Russian Current (RC), and methods associating mechanical and thermal effects on tissue, such as Ultrasound (US), are used to treat GF. US can still be applied with Phonophoresis (Ph) to increase percutaneous absorption of active principles. Objective: To verify the effect of RC associated with US or Ph in the treatment of GF in glutes and thighs of young women. Methods: GF women who performed 10 sessions of RC with US or with Ph participated. The volunteers were evaluated before and after the treatments. Results: There was a reduction in the thickness of the skin folds, reduction of the GF degree, reduction of the body image distortion and high index of satisfaction of the volunteers with the results of both treatments, but the Ph associated to the CR showed a more evident effect. Conclusion: The treatments used provide fast and satisfactory results in the reduction of GF.